INTERNET SAFETY. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article discusses the fundamental concepts of internet safety, its importance, and current online threats. It highlights the dangers users may face while using the internet, such as fraud, identity theft, malware, and cyberbullying. The article also covers protective measures like password security, antivirus software, and the significance of digital literacy. It is especially useful for young people, students, and anyone who actively uses the internet.